2015
DOI: 10.2807/1560-7917.es2015.20.11.21063
|View full text |Cite
|
Sign up to set email alerts
|

Self-sampling for analysis of respiratory viruses in a large-scale epidemiological study in Sweden

Abstract: Viral diagnosis of respiratory tract infections has so far required sampling by health professionals, hampering large-scale epidemiological studies of virus-specific disease outcomes. As part of a population-based, prospective study of work-related risk factors for transmission of viral infections (SWEDE-I), we developed a scheme for self-sampling with nasal swabs. Random selection from the gainfully employed population of a medium-sized town in central Sweden resulted in a study cohort of 2,237 men and women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
5
14
0
Order By: Relevance
“…The viruses most frequently identified were rhino‐/enterovirus, coronaviruses, influenza viruses as well as bocavirus. Except for bocavirus which was not tested in other studies, this finding is in broad agreement with results published by Goff (USA, 2013/2014) and Plymouth (Sweden, 2001/2012) . However, pathogens that are rather detectable in the lower respiratory tract, perhaps particularly bacteria, may not be detectable through this method.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The viruses most frequently identified were rhino‐/enterovirus, coronaviruses, influenza viruses as well as bocavirus. Except for bocavirus which was not tested in other studies, this finding is in broad agreement with results published by Goff (USA, 2013/2014) and Plymouth (Sweden, 2001/2012) . However, pathogens that are rather detectable in the lower respiratory tract, perhaps particularly bacteria, may not be detectable through this method.…”
Section: Discussionsupporting
confidence: 90%
“…During this study, a large variety of viruses was detected. More than 70% of swabs from symptomatic participants yielded at least one pathogen, more than in studies with a similar diagnostic spectrum (36%; 48%). The viruses most frequently identified were rhino‐/enterovirus, coronaviruses, influenza viruses as well as bocavirus.…”
Section: Discussionmentioning
confidence: 92%
“…This may have affected the acceptance to join the project and, consequently, the representativeness of the cohort. However, participation was similar to other recent cohort studies [12, 13], including the 2008–2009 UK Infectious Intestinal Disease study 2 (IID2) and the 2011–2012 Swedish study of work environment and disease epidemiology-infections (SWEDE-I), which had recruitment proportions ranging from 9% to 16%. However, it was lower than older, non-web-based European cohorts: the recruitment proportion of the Infectious intestinal disease study (IID1) conducted in the UK in the 1990s was 35% [14], and for the Sensor study [6] in The Netherlands in 1998–1999, it was 42%.…”
Section: Discussionsupporting
confidence: 70%
“…After collection, swabs may be returned to study staff by mail, dropped off or collected at home by study staff. Several studies have shown self‐collection of nasal swabs among adults to be a feasible and reliable method for ARI surveillance . The Flu Watch Cohort Study followed community cohorts in England over six successive influenza seasons and successfully obtained diagnostic nasal specimens through self‐collection of nasal swabs for more than 85% of ARI episodes .…”
Section: Introductionmentioning
confidence: 99%
“…The Flu Watch Cohort Study followed community cohorts in England over six successive influenza seasons and successfully obtained diagnostic nasal specimens through self‐collection of nasal swabs for more than 85% of ARI episodes . Additionally, a recent study among Swedish adults used nasal self‐swab samples mailed in by participants for virus detection and found that the influenza‐positive test results could be used to measure influenza seasonality . However, to our knowledge, there has not yet been a specific evaluation of self‐collection of nasal swabs by older adults, who may have reduced mobility and cognitive function that could limit their ability to collect valid nasal swabs.…”
Section: Introductionmentioning
confidence: 99%